Pemberdayaan Masyarakat Dalam Early Recovery Pascabencana Melalui Home-Based Livestock dan Gardening Dalam Penguatan Gizi dan Kesejahteraan Masyarakat Menuju Desa Tangguh Bencana di Desa Simpur Jaya - Yusnaini; Devi Annisa Marpaung; Muasir Pagan; Nandara Priyanti Elna; Wirda Hayati; Eva Zulisa; Rhosa Pariana; Illis Khairunnisa (Politeknik Piksi Ganesha Indonesia, 2026)
ABSTRACT: The flood that hit one of the areas in Ketambe District, Southeast Aceh Regency in 2025, namely Simpur Jaya Village, was an event that not only left physical damage, but also shook the social and economic foundations of the community. In this situation, the community faced various limitations including access to basic needs. Carrying out community service activities as a form of real response through student programs that have an impact with a community empowerment approach in assisting post-disaster recovery through home-based livestock and gardening. The purpose of the activity was to increase student awareness of the conditions and needs of disaster-affected communities, support efforts to strengthen community capacity, strengthen the role of student organizations in community empowerment and realize the application of science, technology and innovation according to the needs and potential of the community. The activity was carried out for 20 days. The community service were 3 lecturers from various study programs and 50 students, target partners (farmer groups, livestock breeders and family nutrition groups), and cooperation partners. The method of implementing the activity used the Participatory Action Research method. The results of the activity showed the achievement of the availability of livestock land, chicken and duck coops made from local materials, the availability of vegetable gardens with various types of vegetables such as salad, mustard greens, cayenne pepper and tomatoes, the availability of digital showcases and product promotions in wide reach, as well as ongoing commitment by farmer and livestock groups to achieve results from the development of home-based livestock and home gardening in realizing strengthening nutrition and community welfare.